THE YUGOSLAV ARMY IN THE CONFRONTATION WITH THE NATO AGGRESSION OF 1999 - Djukić, Slobodan (Political Review, 2025)
The political crisis in Kosovo and Metohija, which escalated into an armed conflict between Albanian terrorists and the police forces of the Republic of Serbia, ultimately led to NATO’s military aggression against the Federal Republic of Yugoslavia in 1999. Over the course of 78 days, the Yugoslav Army endured sustained attacks from NATO air forces as well as incursions by Albanian terrorists in Kosovo and Metohija. In the face of a numerically and technologically superior adversary, the Yugoslav Army sought to preserve its personnel and combat assets. Consequently, MiG-29 aircraft were dispersed across multiple airbases, while air defense missile units adopted a scattered combat formation and operated with a reduced engagement of personnel and equipment to minimize losses. Despite its numerical and technological disadvantage, the Yugoslav Army’s Air Defense Corps offered resolute resistance to NATO aviation. Units of the Priština Corps were subjected to intensive NATO airstrikes, as well as assaults by terrorist forces within Kosovo and Metohija. NATO air power significantly restricted the movement and deployment of larger formations within the Priština Corps, forcing them to rely primarily on smaller combat groups equipped with 30/2 mm twin-barreled anti-aircraft cannons (Praga), BRDM armored reconnaissance vehicles, and mortars. Heavier combat assets were employed exclusively under the cover of darkness and in conditions of reduced visibility. Upon completion of combat operations, soldiers would immediately camouflage their tanks to prevent aerial reconnaissance from detecting traces left by their tracks. On April 9, 1999, an assault was launched from the territory of the Republic of Albania against the border outpost at Košare, which terrorist forces managed to overrun during the day. Fighting under extremely challenging conditions on mountainous and forested terrain, Yugoslav Army units—demonstrating extraordinary dedication and self-sacrifice—halted the terrorists’ advance and prevented their deeper penetration into Kosovo and Metohija. NATO aviation played a decisive role in shaping the course of the Battle at Košare, with airstrikes accounting for one-third of all casualties suffered by the Priština Corps. Through its determined and courageous defense, the Yugoslav Army secured an end to NATO’s military aggression against the Federal Republic of Yugoslavia on June 9, 1999, with the signing of the Military-Technical Agreement in Kumanovo and the subsequent adoption of United Nations Security Council Resolution 1244.